The Effect of Participatory Leadership Styles and Organizational Culture on Employee Performance With Employee Engagement as an Intervening Variables (Study at Bali Royal Hospital Denpasar) - Suwandana, Adi; Dwipayanti, Dewi (Universitas Pendidikan Ganesha, 2021)
This study is related to how the direct and indirect influence of participatory leadership style and organizational culture on the employees performance of Bali Royal Hospital Denpasar with employee engagement as an intervening variable. The sampling technique used in this study was the proportionate stratified random sampling technique as many as 97 people who are permanent employees at the Bali Royal Hospital Denpasar. Data is analyzed with classical assumption tests, hypothesis test, path analysis. Analysis was performed using spss version 23 software. The results showed that there was a positive and significant direct influence between participatory leadership style, organizational culture and employee engagement on employee performance. The results showed that the employee engagement variable was not a mediating variable for the influence of participatory leadership style on employee performance, but the employee engagement variable was a mediating variable for the influence of organizational culture on employee performance.